PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. ANGKASA PURA LOGISTIK - zulkarnain, Ade ardian; pogo, Tajuddin (Universitas Mercu Buana, 2019)
Abstract. This study aims to examine and analyze the influence of leadership, work motivation and work discipline on the performance of employees of PT. Angkasa Pura Logistik. The sampling method used is proportional random sampling. From a population of 100 employees with a sample of 80 employees. The method of analysis used in this study is multiple linear regression. The results showed that leadership, work motivation and work discipline together (simultaneously) have a significant effect on performance. Partially, leadership has an insignificant effect on performance. Work motivation and work discipline have a significant positive effect on performance.